حركة التّهذيب والاختصار في التّراث الأدبيّ العربيّ حتّى نهاية القرن السابع الهجريّ - ناصر منال محمود (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
يرصد البحث حركة التّهذيب والاختصار في التّراث الأدبيّ العربيّ, محدّداً مفهوم الاختصار ونشأته في المؤلّفات القديمة , ثم يقف البحث عند بواعث تهذيب الكتب التّراثيّة وأهدافه , ويستعرض مناهج تهذيب هذه الكتب وخصائصه , كما يعرض لمواقف العلماء العرب من حركة التّهذيب والاختصار , ويقدم قراءة نقدية في مختصرات كتاب إصلاح المنطق لابن السّكّيت , بوصفه نموذجاً لكتاب أصلي تعرّض للاختصار والتّهذيب مرّات متعدّدة . This research sheds light on the movement of abridgment and abbreviation Arabic literary heritage , defining and specifying the concept of abbreviation in old scripts and showing the motivations as well as the purposes for abridgment of old books . the research also offer methods and aspects of abridgment those books . it presents Arab scholars view points toward this . the research also provides a critical approach to summaries of Ibn Alsukait s book " Islah Al-mantiq " as a sumple of a book that has been – more than once – asubject to abridgment .